2016
DOI: 10.1111/coa.12723
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and outcome measures seem suboptimal in children with cochlear implants – a cross‐sectional study

Abstract: The most widely used outcome tests after CI, that is CAP and SIR, may not reflect cognitive disabilities sufficiently due to pronounced ceiling effects. International guidelines suggesting a panel of robust age-matched tests are warranted to optimise rehabilitation programmes as well as the counselling of parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…All 21 studies included in the review were published in English between 2002 and 2019. They were conducted in the following countries: the United States ( Pisoni and Cleary, 2003 ; Conway et al, 2011a , b ; Stiles et al, 2012 ; Beer et al, 2014 ; Bharadwaj et al, 2015 ; Meinzen-Derr et al, 2018 ; Davidson et al, 2019 ; McCreery et al, 2019 ), the United Kingdom ( Figueras et al, 2008 ; Edwards and Anderson, 2014 ; Botting et al, 2017 ), Italy ( Bubbico et al, 2007 ; Colletti et al, 2011 ), Australia ( Dawson et al, 2002 ), Saudi Arabia ( Hassan et al, 2014 ), South Korea ( Lee et al, 2012 ), Denmark ( Udholm et al, 2017 ), the Netherlands ( de Hoog et al, 2016 ), Iran ( Soleymani et al, 2016 ), and Taiwan ( Lo and Chen, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All 21 studies included in the review were published in English between 2002 and 2019. They were conducted in the following countries: the United States ( Pisoni and Cleary, 2003 ; Conway et al, 2011a , b ; Stiles et al, 2012 ; Beer et al, 2014 ; Bharadwaj et al, 2015 ; Meinzen-Derr et al, 2018 ; Davidson et al, 2019 ; McCreery et al, 2019 ), the United Kingdom ( Figueras et al, 2008 ; Edwards and Anderson, 2014 ; Botting et al, 2017 ), Italy ( Bubbico et al, 2007 ; Colletti et al, 2011 ), Australia ( Dawson et al, 2002 ), Saudi Arabia ( Hassan et al, 2014 ), South Korea ( Lee et al, 2012 ), Denmark ( Udholm et al, 2017 ), the Netherlands ( de Hoog et al, 2016 ), Iran ( Soleymani et al, 2016 ), and Taiwan ( Lo and Chen, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among them, four studies ( Bubbico et al, 2007 ; Stiles et al, 2012 ; Lo and Chen, 2017 ; McCreery et al, 2019 ) specifically focused on HA users, all of them bilaterally. Eleven studies exclusively approached CI users ( Dawson et al, 2002 ; Pisoni and Cleary, 2003 ; Colletti et al, 2011 ; Conway et al, 2011a , b ; Lee et al, 2012 ; Beer et al, 2014 ; Edwards and Anderson, 2014 ; Bharadwaj et al, 2015 ; Soleymani et al, 2016 ; Udholm et al, 2017 ) and two studies included both groups ( Figueras et al, 2008 ; Hassan et al, 2014 ). Additionally, three studies included participants with bilateral auditory stimulation ( de Hoog et al, 2016 ; Botting et al, 2017 ; Davidson et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Children with better cognitive ability have higher scores in auditory speech. 20 It was found that the mental health of children is not only related to their age at implantation and time of implant usage, but also to their hearing ability and speech intelligibility. Children scoring higher on the Categories of Auditory Performance and Speech Intelligibility Rating Scale spontaneously communicated more with those with normal hearing.…”
Section: Discussionmentioning
confidence: 99%
“…Kromě PPP a dalších specializovaných center najde využití i ve výzkumu (např. Udholm, Aaberg, Bloch, Sandahl & Ovesen, 2017;Kiechl-Kohlendorfer, Ralser, Peglow, Pehboeck-Walser & Fussenegger, 2013…”
Section: Závěryunclassified